578 NUMARALI (1807/1808-1813 M.) (1222-1228 H.) ÜSKÜDAR ŞER'İYYE SİCİLİ - KARASU, FİRDEVS (Fırat Üniveristesi, 2016)
Giriş bölümünde şer'iyye sicilleri, Üsküdar şer'iyye sicilleri hakkında bilgiler verildi ve tezin tanıtımı yapıldı. Daha sonra tezdeki belgelerin kısa özetleri verildi. En sonda da tezdeki belgelerin çevirisini verildi. Anahtar Kelimeler: Osmanlı, Şer'iyye Sicilleri, Şer' i Hukuk, Sicil, Üsküdar, Üsküdar Sicilleri.

Firstly, in introductory chapter we have given information about Court Records Register and Harput Court Records Register also promoted the thesis. Secondly, in main chapter we have given the short summaries of the letters in the thesis. Finally, in conslusion chapter given the translation of the letters in the thesis. Key Words: Ottoman, Court records register, Register, Üsküdar, Üsküdar Court Records Registers.
Üsküdar (1807/1808-1813 M.) (1222-1228 H.) CourtRecords Register dated on (Text Assessment Pages )
Keywords: Tarih